The effect of thickness on ZnO thin film CO gas sensor - Ismail, Yazid Abdul Manakar; Md. Yusuf, Mohd. Nor; Wan Shamsuri, Wan Nurulhuda; Wahab, Yusof; Othaman, Zulkafli (Ibnu Sina Institute for Fundamental Science Studies, UTM, 2006)
Rf magnetron sputtering system were using to deposited ZnO thin films onto corning substrates as a CO gas sensor. The sensing properties of the thin film thickness on CO gas was investigated. The film thickness was varied by controlling the deposition time.The CO gas sensing properties were determined by in situ measurement for surface resistance of the thin film as a function of film thickness, operating temperature and various CO concentrations. The gas sensitivity of ZnO gas sensor depends upon its grain size.